2021
DOI: 10.23889/ijpds.v6i1.1650
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for identification of frailty in Canadian primary care practices

Abstract: IntroductionFrailty is a medical syndrome, commonly affecting people aged 65 years and over and is characterized by a greater risk of adverse outcomes following illness or injury. Electronic medical records contain a large amount of longitudinal data that can be used for primary care research. Machine learning can fully utilize this wide breadth of data for the detection of diseases and syndromes. The creation of a frailty case definition using machine learning may facilitate early intervention, inform advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…Table 1 provides an overview of the selected studies in the frailty screening for ML methods. In general, all studies classified frailty with only one tool, such as the Rockwood Clinical Frailty Scale (CFS) [ 36 ], electronic Frailty Index (eFI) [ 31 ]; frailty phenotype (FP) [ 37 ]; electronic Frailty Score (eFS) [ 5 ]; and an exception that utilized a combination of tools [ 21 ], which included FRS-26-ICD (frailty drawn from ICD-10 Clinical Modification), ECI (The Elixhauser Comorbidity Index (ECI), high-risk medications (10 risk classification, Beers Criteria, 2019), sociodemographic characteristics, healthcare, and insurance utilization. Another exception used a set of predictors variables, including clinical and socioeconomic aspects, and six target variables (mortality, disability, urgent hospitalization, fracture, preventable hospitalization, and accessing the emergency department with red code) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 provides an overview of the selected studies in the frailty screening for ML methods. In general, all studies classified frailty with only one tool, such as the Rockwood Clinical Frailty Scale (CFS) [ 36 ], electronic Frailty Index (eFI) [ 31 ]; frailty phenotype (FP) [ 37 ]; electronic Frailty Score (eFS) [ 5 ]; and an exception that utilized a combination of tools [ 21 ], which included FRS-26-ICD (frailty drawn from ICD-10 Clinical Modification), ECI (The Elixhauser Comorbidity Index (ECI), high-risk medications (10 risk classification, Beers Criteria, 2019), sociodemographic characteristics, healthcare, and insurance utilization. Another exception used a set of predictors variables, including clinical and socioeconomic aspects, and six target variables (mortality, disability, urgent hospitalization, fracture, preventable hospitalization, and accessing the emergency department with red code) [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of features with low variance or high correlation, they reduced the total number of features from 5466 to 75. They used DT, LR, SVM, NB, NN, KNN, RF, and XGBoost models, and the XGBoost was the model with the best results of the eight models which were developed; it achieved the highest sensitivity (78.14%) and specificity (74.41%), but the F1-score was not shown when they used the best threshold that was achieved by using the most optimal thresholds determined using ROC curves [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the primary care setting, Williamson et al used data from the Canadian Primary Care Sentinel Surveillance Network ( n = 875 adults aged over 65 years) to develop the EHR-based frailty definition by machine learning methods and showed that it had the poor predictive ability (sensitivity 28%, specificity 94%) compared with the CFS ( 80 ). However, another study based on the same database with a larger sample improved the predictive ability of this tool by using the XGBoost model (stands for eXtreme Gradient Boosting, is a gradient-boosted decision tree machine learning algorithm) and changing the decision threshold (sensitivity 78.14%, specificity 74.41%) ( 81 ). In addition, machine learning, such as the natural language processing algorithm, may help extract frailty variables from unstructured data in EHRs ( 82 ) and make full use of EHRs in primary care.…”
Section: New Trendsmentioning
confidence: 99%